Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/er.7715
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of solar air heater using a new model of V‐corrugated absorber plate having perforations jets

Abstract: Summary An experimental investigation on the performance of a solar air heater (SAH) system has been performed using a new model of v‐corrugated absorber plate having perforations jets. The effectiveness of new model has been compared with the conventional v‐corrugated absorber plate under identical operating conditions to display the effectiveness of new model. The new collector has been referred to Model‐1, whereas the conventional model has been referred to Model‐2. The experimentations have been conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It was observed that the honeycomb structure increased the maximum heat transfer to the phase change material by 20% and 25%, respectively, at mass flow rates of 0.02 and 0.04 kg/s. Abd et al 48 experimentally investigated the thermal performance of V‐groove absorber plate SAC with perforated jets. In the study, three different mass flow rates as 0.01, 0.015 and 0.02 kg/s were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the honeycomb structure increased the maximum heat transfer to the phase change material by 20% and 25%, respectively, at mass flow rates of 0.02 and 0.04 kg/s. Abd et al 48 experimentally investigated the thermal performance of V‐groove absorber plate SAC with perforated jets. In the study, three different mass flow rates as 0.01, 0.015 and 0.02 kg/s were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research [6,7], artificially rough wires are added to the absorber plate to disrupt the laminar sublayer formulation. In addition, the rate of heat transmission is increased by affixing V-grooves [8,9], corrugations [10,11], turbulators, and baffles [12,13] to the absorber plate and generating local turbulence. In addition, the packed bed, wire meshes, and energy storage materials are attached to the absorber plate to increase its efficiency during periods of low sunlight [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The tests were conducted in both natural and forced convection regimes, and the obtained findings demonstrated that the thermal efficiency of the non-porous and porous solar air heaters (SAHs) reached 81% and 67%, respectively, under forced convection conditions. The empirical study conducted by (Abd et al, 2022a) examined the efficacy of a v-corrugated sheet absorber plate with perforated jets in the context of SHA. The research compared the performance of a novel sheet absorber with that of a conventional corrugated absorber plate.…”
mentioning
confidence: 99%
“…The results indicated that Model 2 had the maximum efficiency level, reaching 67%, while Model 1 obtained an efficiency of 60% at a mass flow rate of 0.02 kg/s. The study conducted by (Abd et al, 2022b) aimed to improve the efficiency of solar air heaters (SAHs) by the modification of V-corrugated absorber plates (APs). The researchers concluded that the altered configuration resulted in a 13.2% enhancement in thermal efficiency compared to the standard configuration.…”
mentioning
confidence: 99%